Constrained compassion: an ethnography exploring compassion in the hospital ward setting - Barnes, Donna (2018)
Ethnography; Compassion; Compassionate care; Nursing A series of healthcare scandals over the last 15 years in the United Kingdom (UK) National Health Service (NHS) generated a vigorous public and professional debate. Within this debate, care failures were framed as a ‘lack of compassion’ and, specifically, a lack of compassion in contemporary nursing.